2021
DOI: 10.1002/fsn3.2105
|View full text |Cite
|
Sign up to set email alerts
|

Consumer acceptance of egg white partially substituted with mushrooms and mushroom–egg white flavor pairing

Abstract: Mushroom possesses a distinctive sensory quality and unique nutrients. Its pairing with egg white and consumer acceptance has never been investigated. In this study, formulated mushroom–egg white patty prototypes (white and crimini mushrooms at 0%, 10%, 20%, and 30%, either oven roasted or steamed) were evaluated by 380 participants for acceptance and intensity of nine sensory attributes. Mushroom–egg white patty prototypes received positive hedonic scores for overall acceptance and the likeability of overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 36 publications
6
24
0
Order By: Relevance
“…Our previous study indicated that consumer acceptance toward egg whitemushroom flavor pairing was positive, ranging from 'either like or dislike' to 'like moderately' for all egg white-mushroom patties. 41 Patties with 10% mushroom had the best egg whitemushroom flavor pairing between mushroom and egg white flavor, regardless of the mushroom type or cooking method. The results confirmed that the ratio between mushroom and egg white was an important factor influencing consumer acceptability.…”
Section: Pls Of Egg-like Flavor and Mushroom-like Flavor Projected Wi...mentioning
confidence: 92%
“…Our previous study indicated that consumer acceptance toward egg whitemushroom flavor pairing was positive, ranging from 'either like or dislike' to 'like moderately' for all egg white-mushroom patties. 41 Patties with 10% mushroom had the best egg whitemushroom flavor pairing between mushroom and egg white flavor, regardless of the mushroom type or cooking method. The results confirmed that the ratio between mushroom and egg white was an important factor influencing consumer acceptability.…”
Section: Pls Of Egg-like Flavor and Mushroom-like Flavor Projected Wi...mentioning
confidence: 92%
“…These results are in line with a similar study in this area of research, wherein sensory evaluation of recipes among Expanded Food and Nutrition Education Program (EFNEP) participants also concluded OL was highly and consistently correlated with the flavor ratings of recipes (Moore et al, 2019). Consumer testing of other food products, both savory (Braghieri, Piazzolla, Carlucci, Bragaglio, & Napolitano, 2016; Du, Muniz, Sissons, Wang, & Juma, 2021; Saint‐Eve, Granda, Legay, Cuvelier, & Delarue, 2019; Wu, Ross, Morris, & Murphy, 2017) and sweet (Andersen, Brockhoff, & Hyldig, 2019; Du et al, 2021; Zhang et al, 2020), have shown similar findings for overall liking and acceptability drivers of liking. Across beverages (Andersen et al, 2019; Zhang et al, 2020) and protein food products (Braghieri et al, 2016; Du et al, 2021), taste and flavor were the primary drivers of overall liking in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Consumer testing of other food products, both savory (Braghieri, Piazzolla, Carlucci, Bragaglio, & Napolitano, 2016; Du, Muniz, Sissons, Wang, & Juma, 2021; Saint‐Eve, Granda, Legay, Cuvelier, & Delarue, 2019; Wu, Ross, Morris, & Murphy, 2017) and sweet (Andersen, Brockhoff, & Hyldig, 2019; Du et al, 2021; Zhang et al, 2020), have shown similar findings for overall liking and acceptability drivers of liking. Across beverages (Andersen et al, 2019; Zhang et al, 2020) and protein food products (Braghieri et al, 2016; Du et al, 2021), taste and flavor were the primary drivers of overall liking in these studies. Texture also strongly impacted the overall liking of these various food products.…”
Section: Discussionmentioning
confidence: 99%
“…Cooked Agaricus bisporus was a good replacer for tomato pulp in the elaboration of ketchup with improved nutritional characteristics and good preferences in 50/50 mushroom/tomato formulations [101]. Likewise, this species was also employed to replace egg white, commonly used as a binder for plant-based meat substitutes, presenting positive hedonic scores, although steaming preparation of mushrooms was preferred over roasting [102]. Egg white is widely used as a binder in plant-based meat substitutes, contributing to the texture of the products during consumption [103].…”
Section: Other Additives Replacermentioning
confidence: 99%
“…Egg white is widely used as a binder in plant-based meat substitutes, contributing to the texture of the products during consumption [103]. For that purpose, Du et al [102] elaborated mushroom-white egg patty prototypes with 10%, 20%, and 30% of white and crimini mushrooms to evaluate several sensory attributes. The addition of mushroom was acceptable up to 20%, with the steam method (water vapor at 163 • C for 10 min) and crimini mushroom being the most preferred.…”
Section: Other Additives Replacermentioning
confidence: 99%